SQSTM1/p62 (sequestosome 1) senses cellular ubiquitin stress through E2-mediated ubiquitination. Issue 6 (3rd June 2018) - Yang, Jiao; Peng, Hong; Xu, Yumin; Xie, Xiaoduo; Hu, Ronggui
ABSTRACT: The alterations in cellular ubiquitin (Ub) homeostasis, known as Ub stress, feature and affect cellular responses in multiple conditions, yet the underlying mechanisms are incompletely understood. We recently reported that the macroautophagy/autophagy receptor SQSTM1/p62, functions as a novel Ub sensor to activate autophagy upon Ub + stress (upregulation of the Ub level). First, SQSTM1 was found to undergo extensive ubiquitination and activate autophagy under Ub + stress induced by prolonged Bortezomib (BTZ) treatment, Ub overexpression or by heat shock. Mechanistically, Ubiquitination of SQSTM1 disrupts its dimerization of the UBA domain, switching it from an auto-inhibitory conformation to recognize poly-ubiquitinated cargoes, promoting autophagic flux. Interestingly, Ub + stress-responsive SQSTM1 ubiquitination is mediated by Ub conjugating enzymes, UBE2D2/3, in a unique E2-dependent manner. Our work has thus revealed a novel mechanism for how SQSTM1 senses cellular Ub stress conditions and regulates selective autophagy in response to diverse intrinsic or extrinsic challenges.